Biodegradation Characteristics of Naphthalene and Benzene, Toluene, Ethyl Benzene, and Xylene (BTEX) by Bacteria Enriched from Activated Sludge. (1st March 2014) - Huang, Yuanxing; Li, Liang
ABSTRACT: : Naphthalene and BTEX (benzene, toluene, ethyl benzene, and xylene) are frequently detected toxic hydrocarbons in contaminated sites, which can easily enter the soil or groundwater system. To test the potential of treating these hydrocarbons in a conventional water resource recovery facility, municipal activated sludge was used as the seed and the bacteria successfully enriched using naphthalene or BTEX as the sole carbon source under aerobic conditions. The pseudo first order kinetic constant for naphthalene degradation by enriched bacteria was 14.053 L h −1 g −1 . For BTEX degradation, kinetic constants of 0.234, 0.958, 1.212, and 0.455 L h −1 g −1 were obtained for benzene, toluene, ethyl benzene, and xylene, respectively, which collectively accounted for a total BTEX removal rate constant of 0.550 L h −1 g −1 . Through cloning and sequencing, Pseudomonas and Burkholderia were identified as the primary bacteria communities in the naphthalene degradation reactor, whereas for BTEX degradation, Pseudomonas and Acidovorax dominated in the reactor.